1990
DOI: 10.1007/bf01797839
|View full text |Cite
|
Sign up to set email alerts
|

Is technetium-99 m-pyrophosphate scintigraphy valuable in the diagnosis of cardiac amyloidosis?

Abstract: Amyloidosis is a systemic disease frequently involving the myocardium and leading to functional disturbances of the heart. Amyloidosis can mimic other cardiac diseases. A conclusive clinical diagnosis of cardiac involvement can only be made by a combination of different diagnostic methods. In 7 patients with myocardial amyloidosis we used a combined first-pass and static scintigraphy with technetium-99 m-pyrophosphate. There was only insignificant myocardial uptake of the tracer. The first-pass studies however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
6

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
5
0
6
Order By: Relevance
“…Various workers have found a positive up take of Tc-99m pyrophosphate in patients with cardiac amyloidosis, especially those with advanced disease [10,[19][20][21], However, others have not found this to be a useful test [22,23]. It is possible that, apart from the severity of amyloid infiltration, the underly ing type of amyloid protein may affect the binding of pyrophosphate in different pa tients.…”
Section: Discussionmentioning
confidence: 93%
“…Various workers have found a positive up take of Tc-99m pyrophosphate in patients with cardiac amyloidosis, especially those with advanced disease [10,[19][20][21], However, others have not found this to be a useful test [22,23]. It is possible that, apart from the severity of amyloid infiltration, the underly ing type of amyloid protein may affect the binding of pyrophosphate in different pa tients.…”
Section: Discussionmentioning
confidence: 93%
“…Assim, a combinação de vários desses achados pode ser factível na realização do diagnóstico. 6,9 Novas técnicas diagnósticas como Doppler tecidual, strain e strain rate permitem o diagnóstico mais precoce da doença, mesmo na ausência de disfunção sistólica. O Doppler tecidual do anel mitral mostrou-se o método com maior acurácia na detecção precoce de disfunção diastólica em pacientes com amiloidose cardíaca.…”
Section: Discussionunclassified
“…Coloração específica com vermelho congo ou coloração imuno-histoquímica ao microscópio com luz polarizada permite identificar seus vários tipos. 6 O tratamento baseia-se na detecção de desordem subjacente e no controle dos sintomas. O transplante cardíaco não apresenta bons resultados em casos avançados devido à frequente recidiva da doença em curto lapso de tempo, sendo raramente indicado devido à progressão da amiloide em outros órgãos e a possibilidade de ocorrer a deposição de amiloide no coração do doador.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The first-pass studies, however, revealed reduced systolic function in four patients and impaired diastolic function in six of the seven patients. They concluded that 99m Tc-PYP scintigraphy is not useful in screening patients for cardiac involvement in amyloidosis, but that first-pass studies yield valuable information about diastolic function impairment [57]. Tanaka et al performed echocardiography and 123 I-MIBG, 201 Tl and 99m Tc-PYP imaging of the heart in 12 patients with familial amyloid polyneuropathy and biopsy-proven cardiac amyloidosis.…”
Section: Amyloid Deposits 99m Tc-aprotininmentioning
confidence: 99%